FACTORS THAT INFLUENCE THE DEVELOPMENT OF EDUCATIONAL STUDY PROBLEMS IN LAMPUYANG STATE PRIMARY SCHOOL - Lisnawati Lisnawati; Siti Mayang Sari (Sensei International Journal of Education and Linguistic, 2024)
Education is a need that must be fulfilled by every individual. Education cannot be separated from all activities carried out by humans. Under any circumstances, humans cannot deny the effects of implementing education in everyday life. Education is divided into three, namely formal education, informal education and non-formal education. The aim of this research is to find out what factors influence the development of educational problems at Lampuyang State Elementary School. This research uses a descriptive qualitative research method, namely research based on phenomena that occurred in one case at Lampuyang State Elementary School. Based on visible facts and interview results obtained, the condition of education at this school is influenced by a number of problems, including a lack of facilities and infrastructure, a lack of textbooks, and the need for better teacher training. Social and cultural factors, such as low economic conditions, also have a significant impact on parental participation in education. Nevertheless, the efforts made, such as improving teacher qualifications, programs involving parents, and initiatives to increase access to technology, reflect positive steps to overcome educational problems at Lampuyang State Elementary School and improve the quality of learning at the school.